The cross-cultural collaboration of the Community Forest. - Robinson, Erin L. (Author); McDonald, Jim (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2008)
Cross-cultural collaboration between First Nations and non-First Nations people in the context of local resource management has not been comprehensively documented in Canada. This thesis will explore how two cultures are collectively managing local land as equal partners. My research has been guided by the question: How can First Nations and non-First Nations communities work together to manage local land in a way that fosters meaningful cross-cultural partnerships and builds sustainable communities? Data about the case study, the Likely-Xats'ull Community Forest, was obtained through ethnography, participant observation and semi-structured interviews. I will discuss the strategies and policies that have been created by citizens at the local level to make this project a success. First Nation citizens from the Xats'ull Nation are collaborating with the non-First Nation community of Likely to create a new social reality by collectively participating to manage a community forest. Local people are exemplifying what can be accomplished when decision-making over land management is carried out at the grassroots level. By working together, local citizens are focusing on similarities as well as common goals and interests that can be improved through cross-cultural work stabilizing local control of the forest with all of its inherent values. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1362345